Fields of knowledge science, politics and publics in the neoliberal age - Frickel, Scott; Hess, David J. (Political power and social theory ;, 2014)
This issue of Political power and social theory explores the changes in science associated with the rise of neoliberalism since the 1970s. The neoliberalization of science has complicated interactions among states, markets, and civil society, often in ways that challenge major assumptions underlying decades of research. The articles collected here break with older Mertonian sociologies of science and constructivist micro-sociologies of scientific knowledge to examine the meso-level problem of the changing institutional contexts of the scientific field as originally identified by Pierre Bourdieu. Papers presented in Part I extend Bourdieús relational approach to the broader set of interactions among scientific, regulatory, industry, and social movement fields. Part II extends Bourdieu's concern with order and the scientific habitus to the changing patterns of scientific practices under neoliberalism. By reconceptualizing the central problem for the social studies of science as the political sociological problem of field and inter-field dynamics, the collected papers chart an important theoretical agenda for future research in the study of science-society relations.